Examination of Complex Traffic Dynamic Systems - Szauter, F.; Péter, T.; Bokor, J. (Acta Technica Jaurinensis, 2013)
A validated, quick and cost-effective alternative method can be applied to analyze driver load, which is based on the track record of the city, traffic simulation model and parameters of the vehicle and driver characteristics.